The relationships between cassava (Manihot esculenta Crantz), ecosystems, diseases and pests and their influence on breeding strategy - Lozano, J.C.; Byrne, D.; Bellotti, Anthony C. (International Center for Tropical Agriculture, 1980)
Based on the considerations related to the characteristics of cassava, centers of origin, and the traditional system of cultivation, several conclusions were made regarding the relationships between the plant and NPFs, constituted by disease and pest pressures and edaphic and climatic factors. It is concluded that: (1) the existence and/or severity of diseases and pest are related to the characteristics of the ecosystem; (2) there appears to be no evidence of race specialization among pathogens and pests of cassava; (3) resistance to NPFs appears to be stable; (4) cassava clones are regionally adapted var.; (5) Manihot esculenta probably has resistance to most NPFs existing in the different ecosystems since it has been selected under a wide range of ecosystems; (6) it is possible to find clones of M. esculenta with resistance to all the NPFs in a given ecosystem; and (7) on the basis of the aforementioned considerations, it is suggested that plant breeding programs should be decentralized to include several representative ecosystems as selection sites. (CIAT)